Currículo e espaços educacionais para bebês no município de Goiânia: um estudo de caso - Malvestio, Silvelene de Alcantara (2023)
The present study is a professional Master's dissertation, linked to the research line School practices and application of knowledge of the Graduate Program in Teaching in Basic Education, of the Center for Applied Research in Education at the Federal University of Goiás. This dissertation presents a research on curriculum and school spaces for babies in an institution of Early Childhood Education after the implementation of the BNCC (Base Nacional Comum Curricular) and the creation of the new Curricular Document of Early Childhood Education of the SME (Secretaria Municipal de Educação e Esporte) from the municipality of Goiânia/GO. The research was carried out based on the following question: How do babies learn and develop in educational spaces and how does the curriculum materialize in this context? To respond to the research problem, expand knowledge and constitute critical thinking about the object, literature review, document analysis and data analysis were used as a methodological path, having historical-dialectical materialism as the epistemological basis. The research and writings of researchers and scholars who are guided by Marx's dialectical historical materialism and Vygotsky's Socio-Historical theory were used, among them: Barbosa (2000), Elkonim (1904- 1984), Vygotsky (1896-1934), Leontieve (1903-1979), Horn (2004), among others. As an educational product, proposals, actions and activities were developed based on the analysis of the data collected in the Child Diagnosis Form Class from 0 to 3 years old, whose objective is to analyze and reflect on the curriculum proposed for babies and very young children and their materialization in the educational unit. The title of the educational product was: The materialization of the curriculum for babies in educational spaces based on their history: the diagnostic form as a basis for building the curriculum. With the analysis and systematization of the Diagnostic Form, it was possible to have some important clues on how to build the curriculum in Early Childhood Education for babies based on their life history. The educational product can be applied, preferably, with teachers and the school community involved in this process of educating babies.